A cross sectional study on stress among doctors, working in college of medicine and Sagore Dutta Hospital, Kamarhati, India - Chatterjee, Supantha; Bhattacharya, Abantika; Bhattacharya, Amiya; Baur, Baijayanti; Madhwani, Kishore P. (International Journal of Advances in Medicine, 2020)
Background: The word “stress” was defined by different scholars. The word was first defined by Hans Selye in 1936 as “a nonspecific response of the body to any demand of change”. The modern medical workplace is a complex environment, and doctors respond differently to it, some finding it stimulating and exciting, whereas others become stressed and burned. The medical workplace also provides an environment where new skills are continually being learned, both as a result of medical knowledge evolving and because a doctor’s work changes. Objective of the present study was to find out the level of stress among the doctors working in CMSDH and to find out the possible sources of stress from their perspective. Methods: The study was an institution-based cross-sectional study conducted from 26th October 2017 to 22nd November 2017 among the enlisted 257 working doctors of CMSDH present during the period of data collection. It was intended to include all the doctors working in this college for this study. Results: A total of 257 doctors including faculty132 (51.4%), interns 80 (31.1%) and house staffs 45 (17.5%) consented and participated in the study of whom 172 (67.0%) were male and 85 (33.0%) female. Interns are the most stressed ones mean 20.4, SD±5.2, followed by house staff mean 17.5, SD±5.1 and faculty mean 16.9, SD±5.3. Unmarried faculty members mean 19.2, SD±5.2 are slightly more stressed than married mean 17.0, SD±5.3. Preclinical faculty has more stress, mean 17.1 ±SD5.2, where the clinical intern has maximum level of stress, mean 20.4 ±SD5.2. Conclusions: Doctors who are in massive stress need counseling and regular psychotherapy to reduce their stress level. A system of monitoring information and communication between administrative and working doctors should be evolved regularly.